Epoxy adhesive film
By using core-shell polymer and A-B-A type triblock copolymer in epoxy films to form a stable graft fusion structure, the existing epoxy films have been solved. The shear strength reduction and thermal stability of the existing epoxy films under high temperature conditions are reduced. The problem is that better bonding performance and thermal stability are achieved, and the scope of application is expanded.
Patent Information
- Application Number
- CN202411710132.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119193068A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to an epoxy adhesive film. Background Art
[0002] Epoxy film, as a high-performance adhesive based on epoxy resin, has shown broad application prospects in many industrial fields due to its unique bonding performance, functional diversity and wide applicability. From home appliance manufacturing to automobile assembly, from electronic device packaging to aerospace technology, epoxy film plays an irreplaceable role. However, despite its wide application, epoxy films in the prior art generally have the problem of insufficient bonding performance, which largely limits the further expansion of its application scope.
[0003] For example, patent application CN111793450A discloses a medium-high temperature cured epoxy film, which exhibits good shear strength at room temperature, but its shear strength decreases significantly under high temperature shear conditions, and its glass transition temperature is low, thus limiting its application range.
[0004] At the same time, some well-known brands of epoxy films on the market, such as Solvay's FM-73 film and 3M's AF126 film, have excellent bonding strength but are weak in thermal stability. After being stored at high temperature for a period of time, the bonding strength will drop significantly.
[0005] Therefore, it is necessary to provide an epoxy film with excellent bonding performance and thermal stability. Summary of the invention
[0006] The purpose of the invention is to solve the problems existing in the prior art and provide an epoxy adhesive film.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] An epoxy film is formed by pressing a rubber compound, which contains 3-10 parts of a core-shell polymer, 3-10 parts of an ABA type triblock copolymer, 60-80 parts of an epoxy resin, and 5-10 parts of a curing agent by weight, wherein the shell material of the core-shell polymer is the same as the A chain segment material of the ABA type triblock copolymer.
[0009] As the preferred technical solution:
[0010] In the epoxy film as described above, the A segment substance of the ABA type triblock copolymer is recorded as substance A, and the B segment substance is recorded as substance B. Substance A is polymethyl methacrylate or polyethyl acrylate, and substance B is polyparaphenylene amide or polybutyl acrylate.
[0011] In the epoxy film as described above, the core layer material of the core-shell polymer is recorded as material C, and material C is polybutadiene rubber, silicone rubber or polybutyl acrylate.
[0012] In the epoxy film as described above, the ABA type triblock copolymer is formed by polymerizing substance A and monomer B under the action of initiator A (n-butyl lithium or sec-butyl lithium), and the core-shell polymer is formed by polymerizing monomer C and substance A under the action of initiator C (tert-butyl hydroperoxide, ammonium persulfate, etc.);
[0013] The preparation process of the ABA type triblock copolymer is as follows: under the protection of nitrogen or inert gas, a part of substance A, monomer B and initiator A are mixed, reacted at 60-90°C for 30-60 minutes, another part of substance A is pumped in to continue the reaction for 30-50 minutes, water or ethanol is slowly added to terminate the reaction, an antioxidant (2,6-di-tert-butyl-p-cresol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-dihydroxybiphenyl, etc.) is added, and after post-treatment (stripping to remove impurities, drying), the ABA type triblock copolymer is obtained, wherein the mass of the part of substance A is 40-60% of the total mass of substance A;
[0014] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 60-80°C for 40-90 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 60-80°C for 40-90 minutes, and after post-treatment (natural cooling to room temperature and filtering through a 200-mesh screen), the core-shell polymer is obtained, wherein the mass of the part of monomer C is 3-8% of the total mass of monomer C.
[0015] In the epoxy film as described above, the curing agent is one or more of dicyandiamide, dimethylimidazole, diaminodiphenyl sulfone, diethylenetriamine and oxalic acid dihydrazide.
[0016] The epoxy adhesive film as described above further comprises 5-10 parts of filler, 1-3 parts of coupling agent and 1-3 parts of accelerator in the adhesive material, calculated by weight.
[0017] For the epoxy film as described above, the steps for preparing the adhesive are as follows:
[0018] (a) The epoxy resin is divided into three parts, which are respectively named epoxy resin 1, epoxy resin 2, and epoxy resin 3;
[0019] (b) mixing epoxy resin 1 and core-shell polymer at 60-80° C. to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 70-95° C. to obtain mixture 2;
[0020] (c) After uniformly mixing mixture 1, mixture 2 and epoxy resin 3, degassing is carried out at 50-95°C for 5-30 minutes, and then curing agent, filler, coupling agent and accelerator are added and mixed uniformly to obtain a rubber compound.
[0021] For the epoxy film as described above, pressing means pressing at 50-95° C. using a calender with the aid of a double-layer release paper or non-woven fabric.
[0022] An epoxy film as described above, the thickness of the epoxy film is 0.1-2 mm; the LOI value of the epoxy film is 30%-32%, and the vertical burning test reaches UL-94 V-0 grade; the roller peel strength of the epoxy film is 90-115 (N•mm) / mm; the shear strength of the epoxy film at 25°C is 28-34 MPa, the shear strength at -20°C or 120°C is 23-27 MPa, and the shear strength at 25°C is maintained at 27-30 MPa after being stored at 50°C for 60 days.
[0023] Principle of the invention:
[0024] The epoxy film of the present invention is prepared by adding a certain amount of core-shell polymer and ABA type triblock copolymer, and controlling the shell material of the core-shell polymer to be the same as the A segment material of the ABA type triblock copolymer, so that the two form a stable graft fusion structure (such as Figure 1 As shown in the figure, when this structure is combined with the interface, it can form a large surface energy through hydrogen bonds or ionic bonds, and then form stable chemical bonds and; when subjected to external force, this structure can effectively absorb energy, induce plastic deformation and shear yield, and at the same time prevent further expansion of cracks, stabilize the glass transition temperature, and thus improve the bonding performance of the epoxy film.
[0025] Beneficial effects:
[0026] (1) The present invention significantly improves the adhesive properties and thermal stability of the epoxy film by precisely controlling the composition and structure of the core-shell polymer and the ABA-type triblock copolymer.
[0027] (2) The epoxy film of the present invention can maintain good shear strength over a wide temperature range, and the decrease in bonding strength after high-temperature storage is small, thereby broadening the application range of the epoxy film and improving its reliability and durability in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the grafted fusion structure formed by the core-shell polymer and the ABA-type triblock copolymer. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0031] LOI value: Tested in accordance with GB / T 2406-93 standard.
[0032] Vertical burning test: Tested in accordance with GB / T 2408-2021 standard.
[0033] Roller peel strength: tested in accordance with GB / T1457-2005 standard; wherein the roller peel speed is 25mm / min.
[0034] Shear strength: tested in accordance with GB / T7124-2008 standard; wherein the tensile speed is 10 mm / min.
[0035] Example 1
[0036] A method for preparing an epoxy film, the specific steps are as follows:
[0037] (1) Preparation of raw materials;
[0038] Substance A: polymethyl methacrylate, CAS number is 9011-14-7;
[0039] Monomer B: p-aminobenzoic acid;
[0040] Antioxidant: 2,6-di-tert-butyl-p-cresol;
[0041] Initiator A: n-butyl lithium;
[0042] Monomer C: 1,3-butadiene;
[0043] Initiator C: tert-butyl hydroperoxide;
[0044] Epoxy resin: Epoxy resin E51, CAS number is 61788-97-4;
[0045] Curing agent: dicyandiamide, particle size ≤50μm;
[0046] Filler: fumed silica, CAS No. 112945-52-5;
[0047] Coupling agent: γ-aminopropyltriethoxysilane;
[0048] Accelerator: 1,1'-(4-methyl-m-phenylene)bis(3,3-dimethylurea);
[0049] (2) Preparation of ABA type triblock copolymers and core-shell polymers;
[0050] The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 60° C. for 30 minutes, another part of substance A is pumped in to continue the reaction for 40 minutes, then the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment; wherein the mass of the part of substance A is 50% of the total mass of substance A, the mass ratio of monomer B to the part of substance A is 1:1, the mass ratio of initiator A to the part of substance A is 1:81, and the mass ratio of antioxidant to the part of substance A is 1:50;
[0051] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 60° C. for 90 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 60° C. for 90 minutes, and the core-shell polymer is obtained through post-treatment; wherein the mass of the part of monomer C is 5% of the total mass of monomer C, the mass ratio of the part of initiator C to the part of monomer C is 1:30, the mass ratio of the other part of initiator C to the part of initiator C is 1:2, and the mass ratio of substance A to the part of initiator C is 300:1;
[0052] (3) preparing rubber;
[0053] (3.1) Divide the epoxy resin into three parts, which are named epoxy resin 1, epoxy resin 2, and epoxy resin 3 respectively;
[0054] (3.2) mixing epoxy resin 1 and core-shell polymer at 60°C to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 70°C to obtain mixture 2;
[0055] (3.3) Mix mixture 1, mixture 2 and epoxy resin 3 evenly, degas at 50°C for 5 minutes, add curing agent, filler, coupling agent and accelerator and mix evenly to obtain a rubber compound;
[0056] The prepared rubber compound contains, by weight, 3 parts of core-shell polymer, 10 parts of ABA type triblock copolymer, 10 parts of epoxy resin 1, 10 parts of epoxy resin 2, 60 parts of epoxy resin 3, 5 parts of curing agent, 5 parts of filler, 1 part of coupling agent and 1 part of accelerator;
[0057] (4) Preparation of epoxy film;
[0058] At 50°C, the adhesive is pressed into an epoxy film using a calender with the aid of a double layer of release paper or non-woven fabric.
[0059] The thickness of the final epoxy film is 0.2mm; the LOI value of the epoxy film is 32%, and the vertical burning test reaches the UL-94 V-0 level; the roller peel strength of the epoxy film is 115 (N•mm) / mm; the shear strength of the epoxy film at 25°C is 34MPa, the shear strength at -20°C is 27MPa, the shear strength at 120°C is 25MPa, and the shear strength at 25°C after storage at 50°C for 60 days is 30MPa.
[0060] Comparative Example 1
[0061] A method for preparing an epoxy film is basically the same as that in Example 1, except that: in step (2), no core-shell polymer is prepared, and in step (3), the core-shell polymer is replaced by an ABA-type triblock copolymer (same as in Example 1) of equal mass.
[0062] The final roller peel strength of the epoxy film is 86 (N•mm) / mm; the shear strength of the epoxy film is 24MPa at 25°C, 22MPa at -20°C, 10MPa at 120°C, and 18MPa at 25°C after storage at 50°C for 60 days.
[0063] Compared with Example 1, the bonding performance and thermal stability of the epoxy film in Comparative Example 1 are significantly reduced. This is because Comparative Example 1 lacks a core-shell polymer to stabilize the glass transition temperature, resulting in a decrease in the mechanical properties of the epoxy film. At the same time, due to the lack of a core-shell polymer, the ABA-type triblock copolymer alone cannot form a more complete stable structure in the epoxy resin, making it impossible to effectively form a large surface energy through hydrogen bonds or ionic bonds when combining with the interface. When subjected to external force, the ability to absorb energy, induce plastic deformation and prevent crack propagation becomes weak, which leads to reduced bonding performance and thermal stability.
[0064] Comparative Example 2
[0065] A method for preparing an epoxy film is basically the same as that in Example 1, except that: in step (2), no ABA type triblock copolymer is prepared, and in step (3), the ABA type triblock copolymer is replaced by an equal mass of a core-shell polymer (the same as in Example 1).
[0066] The final roller peel strength of the epoxy film is 75 (N•mm) / mm; the shear strength of the epoxy film is 25MPa at 25°C, 24MPa at -20°C, 17MPa at 120°C, and 20MPa at 25°C after being stored at 50°C for 60 days.
[0067] Compared with Example 1, the bonding performance and thermal stability of the epoxy film in Comparative Example 2 are significantly reduced. This is because Comparative Example 2 lacks an ABA-type triblock copolymer, and the core-shell polymer alone cannot form a more complete and stable structure in the epoxy resin, resulting in an inability to effectively form a large surface energy through hydrogen bonds or ionic bonds when combined with the interface. As a result, when subjected to external forces, the ability to absorb energy, induce plastic deformation, and prevent crack propagation is weakened, so the bonding performance and thermal stability are significantly reduced.
[0068] Comparative Example 3
[0069] A method for preparing an epoxy film is basically the same as Example 1, except that when preparing the core-shell polymer, substance A is replaced with an equal mass of silicon dioxide.
[0070] The final roller peel strength of the epoxy film is 84 (N•mm) / mm; the shear strength of the epoxy film is 21MPa at 25°C, 20MPa at -20°C, 15MPa at 120°C, and 15MPa at 25°C after being stored at 50°C for 60 days.
[0071] Compared with Example 1, the bonding performance and thermal stability of the epoxy film in Comparative Example 3 are significantly reduced. This is because the shell material of the core-shell polymer in Comparative Example 3 is silicon dioxide, which has poor fusion with the A segment material of the ABA-type triblock copolymer, resulting in the inability of the two to form an effective grafted fusion structure in the epoxy resin. This structural mismatch makes it impossible to fully utilize hydrogen bonds or ionic bonds to form a larger surface energy when combining with the interface, and it is impossible to work together when subjected to external forces, and it is impossible to effectively induce plastic deformation, shear yield, and prevent crack propagation. The overall structural stability is damaged, and ultimately the bonding performance and thermal stability are significantly reduced.
[0072] Example 2
[0073] A method for preparing an epoxy film is basically the same as that of Example 1, except that no filler, coupling agent or accelerator is added in step (3).
[0074] The final roller peel strength of the epoxy film is 104 (N•mm) / mm; the shear strength of the epoxy film is 30MPa at 25°C, 29MPa at -20°C, 23MPa at 120°C, and 27MPa at 25°C after storage at 50°C for 60 days.
[0075] Example 3
[0076] A method for preparing an epoxy film, the specific steps are as follows:
[0077] (1) Preparation of raw materials;
[0078] Substance A: polymethyl methacrylate, CAS number is 9011-14-7;
[0079] Monomer B: p-aminobenzoic acid;
[0080] Antioxidant: 2,2'-methylenebis(4-methyl-6-tert-butylphenol);
[0081] Initiator A: sec-butyllithium;
[0082] Monomer C: vinyl silane;
[0083] Initiator C: ammonium persulfate;
[0084] Epoxy resin: Epoxy resin E42, CAS number is 25085-99-8;
[0085] Curing agent: a mixture of dicyandiamide (particle size ≤ 50 μm) and dimethylimidazole in a mass ratio of 5:1;
[0086] Filler: silica powder, CAS number is 7440-21-3;
[0087] Coupling agent: γ-glycidyloxypropyltrimethoxysilane;
[0088] Accelerator: 1,1'-(4-methyl-m-phenylene)bis(3,3-dimethylurea);
[0089] (2) Preparation of ABA type triblock copolymers and core-shell polymers;
[0090] The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 60° C. for 60 minutes, another part of substance A is pumped in to continue the reaction for 50 minutes, then the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment; wherein the mass of the part of substance A is 40% of the total mass of substance A, the mass ratio of monomer B to the part of substance A is 1:1, the mass ratio of initiator A to the part of substance A is 1:80, and the mass ratio of antioxidant to the part of substance A is 1:65;
[0091] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 70° C. for 40 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 80° C. for 90 minutes, and after post-treatment, a core-shell polymer is obtained; wherein the mass of the part of monomer C is 3% of the total mass of monomer C, the mass ratio of the part of initiator C to the part of monomer C is 1:31, the mass ratio of the other part of initiator C to the part of initiator C is 1:1, and the mass ratio of substance A to the part of initiator C is 302:1;
[0092] (3) preparing rubber;
[0093] (3.1) Divide the epoxy resin into three parts, which are named epoxy resin 1, epoxy resin 2, and epoxy resin 3 respectively;
[0094] (3.2) mixing epoxy resin 1 and core-shell polymer at 60°C to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 70°C to obtain mixture 2;
[0095] (3.3) Mix mixture 1, mixture 2 and epoxy resin 3 evenly, degas at 70°C for 10 min, add curing agent, filler, coupling agent and accelerator and mix evenly to obtain a rubber compound;
[0096] The prepared rubber compound contains, by weight, 4 parts of core-shell polymer, 9 parts of ABA type triblock copolymer, 15 parts of epoxy resin 1, 15 parts of epoxy resin 2, 50 parts of epoxy resin 3, 6 parts of curing agent, 5 parts of filler, 1 part of coupling agent and 3 parts of accelerator;
[0097] (4) Preparation of epoxy film;
[0098] At 80°C, the adhesive is pressed into an epoxy film using a calender with the aid of a double layer of release paper or non-woven fabric.
[0099] The thickness of the final epoxy film is 0.1mm; the LOI value of the epoxy film is 30%, and the vertical burning test reaches the UL-94 V-0 level; the roller peel strength of the epoxy film is 98 (N•mm) / mm; the shear strength of the epoxy film is 29MPa at 25°C, 27MPa at -20°C, 27MPa at 120°C, and 28MPa at 25°C after storage at 50°C for 60 days.
[0100] Example 4
[0101] A method for preparing an epoxy film, the specific steps are as follows:
[0102] (1) Preparation of raw materials;
[0103] Substance A: polymethyl methacrylate, CAS number is 9011-14-7;
[0104] Monomer B: butyl acrylate;
[0105] Antioxidant: 4,4'-dihydroxybiphenyl;
[0106] Initiator A: n-butyl lithium;
[0107] Monomer C: 1,3-butadiene;
[0108] Initiator C: tert-butyl hydroperoxide;
[0109] Epoxy resin: Epoxy resin E44, CAS number is 38891-59-7;
[0110] Curing agent: diaminodiphenyl sulfone;
[0111] Filler: fumed silica, CAS No. 112945-52-5;
[0112] Coupling agent: γ-methacryloxypropyltrimethoxysilane;
[0113] Accelerator: dimethyl imidazole urea;
[0114] (2) Preparation of ABA type triblock copolymers and core-shell polymers;
[0115] The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 70° C. for 50 minutes, another part of substance A is pumped in to continue the reaction for 30 minutes, then the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment; wherein the mass of the part of substance A is 50% of the total mass of substance A, the mass ratio of monomer B to the part of substance A is 1:1, the mass ratio of initiator A to the part of substance A is 1:79, and the mass ratio of antioxidant to the part of substance A is 1:50;
[0116] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 80° C. for 60 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 60° C. for 80 minutes, and the core-shell polymer is obtained through post-treatment; wherein the mass of the part of monomer C is 8% of the total mass of monomer C, the mass ratio of the part of initiator C to the part of monomer C is 1:25, the mass ratio of the other part of initiator C to the part of initiator C is 1:2, and the mass ratio of substance A to the part of initiator C is 305:1;
[0117] (3) preparing rubber;
[0118] (3.1) Divide the epoxy resin into three parts, which are named epoxy resin 1, epoxy resin 2, and epoxy resin 3 respectively;
[0119] (3.2) mixing epoxy resin 1 and core-shell polymer at 70°C to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 80°C to obtain mixture 2;
[0120] (3.3) Mix mixture 1, mixture 2 and epoxy resin 3 evenly, degas at 95°C for 30 minutes, add curing agent, filler, coupling agent and accelerator and mix evenly to obtain a rubber compound;
[0121] The prepared rubber compound contains, by weight, 6 parts of core-shell polymer, 7 parts of ABA type triblock copolymer, 10 parts of epoxy resin 1, 10 parts of epoxy resin 2, 40 parts of epoxy resin 3, 7 parts of curing agent, 10 parts of filler, 3 parts of coupling agent and 1 part of accelerator;
[0122] (4) Preparation of epoxy film;
[0123] At 95°C, the adhesive is pressed into an epoxy film using a calender with the aid of a double-layer release paper or non-woven fabric.
[0124] The thickness of the final epoxy film is 0.1mm; the LOI value of the epoxy film is 30%, and the vertical burning test reaches the UL-94 V-0 level; the roller peel strength of the epoxy film is 100 (N•mm) / mm; the shear strength of the epoxy film at 25°C is 30MPa, the shear strength at -20°C is 27MPa, the shear strength at 120°C is 26MPa, and the shear strength at 25°C after storage at 50°C for 60 days is 27MPa.
[0125] Example 5
[0126] A method for preparing an epoxy film, the specific steps are as follows:
[0127] (1) Preparation of raw materials;
[0128] Substance A: polyethyl acrylate, CAS number 9003-32-1;
[0129] Monomer B: p-aminobenzoic acid;
[0130] Antioxidant: 2,6-di-tert-butyl-p-cresol;
[0131] Initiator A: sec-butyllithium;
[0132] Monomer C: butyl acrylate;
[0133] Initiator C: tert-butyl hydroperoxide;
[0134] Epoxy resin: Epoxy resin F51, CAS number is 24969-06-0;
[0135] Curing agent: diethylenetriamine;
[0136] Filler: silica powder, CAS number is 7440-21-3;
[0137] Coupling agent: γ-mercaptopropyltriethoxysilane;
[0138] Accelerator: 1,1'-(4-methyl-m-phenylene)bis(3,3-dimethylurea);
[0139] (2) Preparation of ABA type triblock copolymers and core-shell polymers;
[0140] The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 80° C. for 60 minutes, another part of substance A is pumped in to continue the reaction for 50 minutes, then the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment; wherein the mass of the part of substance A is 50% of the total mass of substance A, the mass ratio of monomer B to the part of substance A is 1:1, the mass ratio of initiator A to the part of substance A is 1:78, and the mass ratio of antioxidant to the part of substance A is 1:60;
[0141] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 60° C. for 90 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 60° C. for 40 minutes, and the core-shell polymer is obtained through post-treatment; wherein the mass of the part of monomer C is 5% of the total mass of monomer C, the mass ratio of the part of initiator C to the part of monomer C is 1:30, the mass ratio of the other part of initiator C to the part of initiator C is 1:2, and the mass ratio of substance A to the part of initiator C is 301:1;
[0142] (3) preparing rubber;
[0143] (3.1) Divide the epoxy resin into three parts, which are named epoxy resin 1, epoxy resin 2, and epoxy resin 3 respectively;
[0144] (3.2) mixing epoxy resin 1 and core-shell polymer at 70°C to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 95°C to obtain mixture 2;
[0145] (3.3) Mix mixture 1, mixture 2 and epoxy resin 3 evenly, degas at 95°C for 5 minutes, and then add curing agent, filler, coupling agent and accelerator and mix evenly to obtain a rubber compound;
[0146] The prepared rubber compound contains, by weight, 8 parts of core-shell polymer, 5 parts of ABA type triblock copolymer, 20 parts of epoxy resin 1, 20 parts of epoxy resin 2, 40 parts of epoxy resin 3, 8 parts of curing agent, 5 parts of filler, 1 part of coupling agent and 2 parts of accelerator;
[0147] (4) Preparation of epoxy film;
[0148] At 50°C, the adhesive is pressed into an epoxy film using a calender with the aid of a double layer of release paper or non-woven fabric.
[0149] The final epoxy film has a thickness of 2 mm; the LOI value of the epoxy film is 31%, and the vertical burning test reaches the UL-94 V-0 level; the roller peel strength of the epoxy film is 90 (N•mm) / mm; the shear strength of the epoxy film is 28 MPa at 25°C, 25 MPa at -20°C, 25 MPa at 120°C, and 27 MPa at 25°C after storage at 50°C for 60 days.
[0150] Example 6
[0151] A method for preparing an epoxy film, the specific steps are as follows:
[0152] (1) Preparation of raw materials;
[0153] Substance A: polyethyl acrylate, CAS number 9003-32-1;
[0154] Monomer B: butyl acrylate;
[0155] Antioxidant: 4,4'-dihydroxybiphenyl;
[0156] Initiator A: n-butyl lithium;
[0157] Monomer C: 1,3-butadiene;
[0158] Initiator C: ammonium persulfate;
[0159] Epoxy resin: Epoxy resin E42, CAS number is 25085-99-8;
[0160] Curing agent: a mixture of dicyandiamide (particle size ≤ 50 μm) and oxalic acid dihydrazide in a mass ratio of 3:1;
[0161] Filler: fumed silica, CAS No. 112945-52-5;
[0162] Coupling agent: vinyltrimethoxysilane;
[0163] Accelerator: dimethyl imidazole urea;
[0164] (2) Preparation of ABA type triblock copolymers and core-shell polymers;
[0165] The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 90° C. for 60 minutes, another part of substance A is pumped in to continue the reaction for 40 minutes, then the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment; wherein the mass of the part of substance A is 60% of the total mass of substance A, the mass ratio of monomer B to the part of substance A is 1:1, the mass ratio of initiator A to the part of substance A is 1:80, and the mass ratio of antioxidant to the part of substance A is 1:55;
[0166] The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 80° C. for 80 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 80° C. for 80 minutes, and the core-shell polymer is obtained through post-treatment; wherein the mass of the part of monomer C is 6% of the total mass of monomer C, the mass ratio of the part of initiator C to the part of monomer C is 1:30, the mass ratio of the other part of initiator C to the part of initiator C is 1:1, and the mass ratio of substance A to the part of initiator C is 302:1;
[0167] (3) preparing rubber;
[0168] (3.1) Divide the epoxy resin into three parts, which are named epoxy resin 1, epoxy resin 2, and epoxy resin 3 respectively;
[0169] (3.2) epoxy resin 1 and core-shell polymer were mixed at 80°C to obtain mixture 1, and epoxy resin 2 and ABA triblock copolymer were mixed at 95°C to obtain mixture 2;
[0170] (3.3) Mix mixture 1, mixture 2 and epoxy resin 3 evenly, degas at 80°C for 15 minutes, add curing agent, filler, coupling agent and accelerator and mix evenly to obtain a rubber compound;
[0171] The prepared rubber compound contains, by weight, 10 parts of core-shell polymer, 3 parts of ABA type triblock copolymer, 15 parts of epoxy resin 1, 15 parts of epoxy resin 2, 40 parts of epoxy resin 3, 10 parts of curing agent, 8 parts of filler, 1 part of coupling agent and 1 part of accelerator;
[0172] (4) Preparation of epoxy film;
[0173] At 70°C, the adhesive is pressed into an epoxy film using a calender with the aid of a double-layer release paper or non-woven fabric.
[0174] The thickness of the final epoxy film is 0.5mm; the LOI value of the epoxy film is 30%, and the vertical burning test reaches the UL-94 V-0 level; the roller peel strength of the epoxy film is 110 (N•mm) / mm; the shear strength of the epoxy film at 25°C is 31MPa, the shear strength at -20°C is 27MPa, the shear strength at 120°C is 25MPa, and the shear strength at 25°C after storage at 50°C for 60 days is 28MPa.
Claims
1. An epoxy film, formed by pressing a rubber compound, characterized in that: By weight, the rubber material contains 3-10 parts of core-shell polymer, 3-10 parts of ABA type triblock copolymer, 60-80 parts of epoxy resin and 5-10 parts of curing agent, wherein the shell material of the core-shell polymer is the same as the A segment material of the ABA type triblock copolymer.
2. The epoxy film according to claim 1, characterized in that: The A segment substance of the ABA type triblock copolymer is recorded as substance A, and the B segment substance is recorded as substance B. Substance A is polymethyl methacrylate or polyethyl acrylate, and substance B is polyparaphenylene amide or polybutyl acrylate.
3. An epoxy film according to claim 2, characterized in that: The core layer material of the core-shell polymer is recorded as material C, and material C is polybutadiene rubber, silicone rubber or polybutyl acrylate.
4. The epoxy film according to claim 3, characterized in that: The ABA type triblock copolymer is formed by polymerizing substance A and monomer B under the action of initiator A, and the core-shell polymer is formed by polymerizing monomer C and substance A under the action of initiator C; The preparation process of the ABA type triblock copolymer is as follows: a part of substance A, monomer B and initiator A are mixed, reacted at 60-90° C. for 30-60 minutes, another part of substance A is pumped in to continue the reaction for 30-50 minutes, the reaction is terminated, an antioxidant is added, and the ABA type triblock copolymer is obtained after post-treatment, wherein the mass of the part of substance A is 40-60% of the total mass of substance A; The preparation process of the core-shell polymer is as follows: a part of monomer C and a part of initiator C are mixed, reacted at 60-80°C for 40-90 minutes, and then another part of monomer C and another part of initiator C are pumped in. After the feeding of monomer C is completed, substance A is pumped in. After the feeding of initiator C is completed, the reaction is carried out at a constant temperature of 60-80°C for 40-90 minutes, and the core-shell polymer is obtained after post-treatment, wherein the mass of the part of monomer C is 3-8% of the total mass of monomer C.
5. An epoxy film according to any one of claims 2 to 4, characterized in that: The curing agent is one or more of dicyandiamide, dimethylimidazole, diaminodiphenyl sulfone, diethylenetriamine and oxalic acid dihydrazide.
6. The epoxy film according to claim 5, characterized in that: By weight, the rubber compound also contains 5-10 parts of filler, 1-3 parts of coupling agent and 1-3 parts of accelerator.
7. The epoxy film according to claim 6, characterized in that: The steps for preparing the rubber compound are as follows: (a) The epoxy resin is divided into three parts, which are respectively named epoxy resin 1, epoxy resin 2, and epoxy resin 3; (b) mixing epoxy resin 1 and core-shell polymer at 60-80° C. to obtain mixture 1, and mixing epoxy resin 2 and ABA triblock copolymer at 70-95° C. to obtain mixture 2; (c) After uniformly mixing mixture 1, mixture 2 and epoxy resin 3, degassing is carried out at 50-95°C for 5-30 minutes, and then curing agent, filler, coupling agent and accelerator are added and mixed uniformly to obtain a rubber compound.
8. The epoxy film according to claim 5, characterized in that: Pressing refers to pressing at 50-95°C using a calender with the aid of double-layer release paper or non-woven fabric.
9. The epoxy film according to claim 8, characterized in that: The thickness of the epoxy film is 0.1-2mm; the LOI value of the epoxy film is 30%-32%, and the vertical burning test reaches UL-94 V-0 grade; the roller peel strength of the epoxy film is 90-115 (N•mm) / mm; the shear strength of the epoxy film at 25°C is 28-34MPa, and the shear strength at -20°C or 120°C is 23-27MPa. After being stored at 50°C for 60 days, the shear strength at 25°C is maintained at 27-30MPa.
Citation Information
Patent Citations
Medium-high temperature cured epoxy structural adhesive film with thermal breaking performance applied to sound absorption and noise reduction honeycomb plate and preparation method thereof
CN111793450A
High-tenacity bismaleimide resin carrier structure adhesive film and preparation method thereof
CN103242768A
Halogen-free flame-retardant carbon fiber reinforced polycarbonate composition as well as preparation method and application thereof
CN114621573A
Inkjet recording sheet
JP2004050555A
Method for manufacturing metal phase transition-based flexible electronic material and application of same
WO2023197491A1
